THE USE OF MODIS DATA TO EXTRACT A DUST STORM PRODUCT - Faten G. Abed; Abed Alkareem Abed Ali; Eshtar H. Nasser (BRIN, 2012)
Iraq in the summer is affected by low pressure centered in the area of Arabian Sea and the Indian Ocean, and the high pressure region in the plateau of Anatolia. This climate system causes that the Shamal wind blows from the plateau of Anatolia in the north and northwest with relatively cold temperature. From mid-June to mid-September, the wind is accompanied with intensive heating of the earth surface causing dust storms rising up to thousand meters in the atmosphere above Iraq region. In recent years, the frequency of dust storm events was increased in Iraq and its surrounding regions due to the long drought seasons. Unsupervised classification method was used to determine the intensity of the dust storm and to identify the area of dust cloud. In this study, we were able to map dust storm over Iraq region using MODIS Terra and Aqua satellite data within thermal bands (band 31 and 32), and visible band VIS (band 1). Other thermal band (band 21) was used to produce RGB composite image specifying the dust storm. A spectral subtraction between two bands was also used to produce another RGB composite image to obtain better detection for the dust storm over Iraq region.